2015
DOI: 10.1021/jacs.5b07931
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Transforming Mineral Phases in Fresh Nacre

Abstract: Nacre, or mother-of-pearl, the iridescent inner layer of many mollusk shells, is a biomineral lamellar composite of aragonite (CaCO3) and organic sheets. Biomineralization frequently occurs via transient amorphous precursor phases, crystallizing into the final stable biomineral. In nacre, despite extensive attempts, amorphous calcium carbonate (ACC) precursors have remained elusive. They were inferred from non-nacre-forming larval shells, or from a residue of amorphous material surrounding mature gastropod nac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
191
1
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(210 citation statements)
references
References 129 publications
11
191
1
7
Order By: Relevance
“…While our reaction conditions are significantly different from those used by organisms during biomineralization, our results demonstrate that this non‐classical pathway is a possible route for the precipitation of aragonite. The similarity of the particle attachment mechanisms observed in forming biominerals4d, 9e, 15 and in vitro suggests that a similar mechanism is indeed possible in biogenic systems. Further work is required to confirm this hypothesis.…”
mentioning
confidence: 76%
“…While our reaction conditions are significantly different from those used by organisms during biomineralization, our results demonstrate that this non‐classical pathway is a possible route for the precipitation of aragonite. The similarity of the particle attachment mechanisms observed in forming biominerals4d, 9e, 15 and in vitro suggests that a similar mechanism is indeed possible in biogenic systems. Further work is required to confirm this hypothesis.…”
mentioning
confidence: 76%
“…However, a number of investigations have concluded that the non-classical growth mechanism of aggregation and coalescence of nanoparticles is a common phenomenon in biomineral [90][91][92], biomimetic [93][94][95], environmental [95][96][97], and synthetic systems [8,60,[98][99][100][101][102][103][104][105][106]. The resulting crystals can exhibit complex morphologies such as quasi-one dimensional chains, highly branched nanowires, and 3D hierarchical and self-similar superstructures [107].…”
Section: Discussionmentioning
confidence: 99%
“…[66] In sea urchin spines, ACC is transformed into calcite; however, systematic investigations of sea urchin spines resulted in the discovery of different kinds of ACC and uncovering their stabilization mechanisms. [75] Furthermore, there are indications that the amorphous calcium phosphate phase, which is the major mineral phase in the newly formed parts of the zebrafish fin bone, is a precursor of crystalline carbonated hydroxyapatite. [72,73] Later on, an amorphous layer, covering nacre lamellae, was observed in Haliotis laevigata abalone shells.…”
Section: Physical Origin Of Anisotropic Lattice Distortionsmentioning
confidence: 99%